Single and composed configuration of perceptual cues on the anticipation of tennis serves - Zawadzki, P.; Roca, J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Players are common required to fit their responses under a variety of strokes of different opponents. On the tennis serve devolution this becomes evident because of anticipation requirement (Farrow and Abernethy, 2002). During association of perceptual cues to response, two functional ways can be establish: constancy between elements or configuration between values of elements (Roca, 2006). The aim of this study was compare the analyses of two single cases approximating the concepts of Model Field Theory to Statistical Correlation Theory to verify the existence of both cases. Methods: One female and one male tennis professionals were recorded during an official match, kinematics method were used to digitise polar coordinates of four perceptual cues (position, ball toss, knee bend and racket arm). Pearson Correlation (r) and Canonical Correlation Analysis (Rc) were performed between perceptual cues and bounce result. Results: On the female case a single perceptual cue were founded, significative results shows the height of ball toss correlated to serve depth (r=0.887, p<0.01). On the male case significative results were found but with no power (r<0.5) of prediction on the single cues, however, composed cues presented values of Rc=0.9098 (p=0.0104) presenting similar weights for position (cv=0.1601) and ball toss (cv=-0.1365) however with different directions on the relationship. No results were found about constancy on perceptual cues. Discussion: Associations between values of elements were found, the power related serve as evidence to support perceptive configuration theory. Nonetheless, results also suggest two ways of configuration, one established by the relationship of just two variables or cues, called here as single configuration and another established by the relationship between one cue with a group or between two groups of cues, called here as composed configuration. Ventura (2004) demonstrated that a reduction of performance is observed when the grade of variability increase; what could propose that during player development a technique disguise occurs and through that more than one cue must be perceived by his opponent. In any case, the Opponent Study in Sport reveals itself as field plenty of opportunities to help players to fit better their responses.